Unleashing the art of digital forensics - Kaushik, Keshav; Tanwar, Rohit; Dahiya, Susheela; Bhatia, Komal, 1979-; Wu, Yulei (Boca Raton : Chapman & Hall/CRC Press, 2023)
"Unleashing the Art of Digital Forensics is intended to describe and explain the steps taken during a forensic examination, with the intent of making the reader aware of the constraints and considerations that apply during a forensic examination in law enforcement and in the private sector. The book is aimed primarily at graduates, postgraduates and researchers in digital forensics and cybersecurity"--
Data hiding : steganography and steganalysis / K.N.D. Saile, V.Y. Bharadwaj and G.Y. Vybhavi -- International cyber space laws / Manik Garg, Susheela Dahiya and Keshav Kaushik -- Unraveling the Deep and Dark Web / Susheela Dahiya, Manik Garg and Keshav Kaushik -- Memory acquisition process for the Linux and Macintosh based operating system using opensource tool / Ravi Sheth and Ashish Shukla -- Deepfakes : a looming threat to our society / Raahat Devender Singh -- Challenges in digital forensics and future aspects / Shreyas Muthye -- Cyber crimes against women in India : how can the law and the technology help the victims? / Sujata Bali -- Anti money laundering : role of machine learning / Smita Pachare, Suhasini Verma and Vidhisha Vyas -- Lightweight approach for integrity : a novel cryptographic hash function / Pooja S., Vikas Sagar and Rohit Tanwar -- Memory acquisition and analysis for forensic investigation / Tripti Misra, Vanshika Singh and Tanisha Singla -- Forensics in medical imaging : techniques and tools / Bhavana Kaushik and Keshav Kaushik -- Exploring face detection and recognition in steganography / Urmila Pilania and Rohit Tanwar -- Authentication and admissibility of forensic evidence under Indian criminal justice delivery system : an analysis / Sujata Bali and Bharti Nair Khan.
OCLC-licensed vendor bibliographic record.
Keywords: Digital forensic science -- India -- Case studies; Computer security -- India -- Case studies; Computer crimes -- Investigation -- India -- Case studies; COMPUTERS / Computer Engineering; COMPUTERS / Networking / Security; COMPUTERS / Internet / Security